2019
DOI: 10.1097/md.0000000000016115
|View full text |Cite
|
Sign up to set email alerts
|

The effect of magnesium sulfate on surgical field during endoscopic sinus surgery

Abstract: Introduction: The benefits of magnesium sulfate for surgical field during endoscopic sinus surgery remain controversial. We conduct a systematic review and meta-analysis to explore the influence of magnesium sulfate versus placebo on surgical field during endoscopic sinus surgery. Methods: We search PubMed, EMbase, Web of science, EBSCO, and Cochrane library databases through November 2018 for randomized controlled trials (RCTs) assessing the effect of magnesium sulfate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
(33 reference statements)
1
2
0
Order By: Relevance
“…In our study, additional 0.5 mcg/kg fentanyl was given if the heart rate and systolic blood pressure increased more than 20%, was comparable in both groups, and was found to be statistically insignificant. Liu et al conducted a study in which there was no significant reduction in the requirement for fentanyl, which is similar to our study [12].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, additional 0.5 mcg/kg fentanyl was given if the heart rate and systolic blood pressure increased more than 20%, was comparable in both groups, and was found to be statistically insignificant. Liu et al conducted a study in which there was no significant reduction in the requirement for fentanyl, which is similar to our study [12].…”
Section: Discussionsupporting
confidence: 90%
“…This finding is consistent with the study by Liu et al, who also compared the use of MgSO 4 with placebo in patients undergoing endoscopic sinus surgery. They concluded that MgSO 4 was associated with a significantly lower amount of intraoperative blood loss and improved the surgical field grading as compared to a placebo [12].…”
Section: Discussionmentioning
confidence: 99%
“…Procedures with heightened hemodynamic challenges or those requiring prolonged airway management may warrant a more proactive approach to maintain stability, making MgSO 4 a strategic choice in the overall perioperative management of ENT surgeries. This patientcentric and procedure-specific approach enhances the precision and efficacy of MgSO 4 infusion in the ENT setting [32].…”
Section: Patient Selection Criteriamentioning
confidence: 98%